1993
DOI: 10.1007/bf00593967
|View full text |Cite
|
Sign up to set email alerts
|

Age distribution and iron dependency of the T2 relaxation time in the globus pallidus and putamen

Abstract: Heavily T2-weighted spin echo sequences of the brain show age-dependent low signal intensity in many extrapyramidal nuclei. Although it has been suggested that this low intensity results from non-haem iron, the specific influence of non-haem iron on the T2 relaxation time has not been quantified and remains controversial. The T2 relaxation times of the globus pallidus and putamen were measured from MRI at 1.5T in 27 healthy patients, by using a mathematical model. They were then plotted as a function of age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
2
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 20 publications
10
78
2
1
Order By: Relevance
“…The volume-corrected intensities for the globus pallidus and putamen essentially plateau by the fifth decade, whereas the red nucleus and substantia nigra continue to have a gradually declining intensity through life. These findings agree quite well with the landmark work of Hallgren and Sourander 1 as well as with the iron-staining experiments by Drayer et al 17 The initial rapid mineralization of the globus pallidus has been reported in other MR studies, 14,15,31 though there is some disagreement about what occurs later in life. Hallgren and Sourander 1 and Schenker et al 31 postulate that the globus pallidus reaches iron saturation before the age of 40, whereas Milton et al 14 observe that middle-aged and elderly adults show increased iron content compared with young adults.…”
Section: Discussionsupporting
confidence: 91%
“…The volume-corrected intensities for the globus pallidus and putamen essentially plateau by the fifth decade, whereas the red nucleus and substantia nigra continue to have a gradually declining intensity through life. These findings agree quite well with the landmark work of Hallgren and Sourander 1 as well as with the iron-staining experiments by Drayer et al 17 The initial rapid mineralization of the globus pallidus has been reported in other MR studies, 14,15,31 though there is some disagreement about what occurs later in life. Hallgren and Sourander 1 and Schenker et al 31 postulate that the globus pallidus reaches iron saturation before the age of 40, whereas Milton et al 14 observe that middle-aged and elderly adults show increased iron content compared with young adults.…”
Section: Discussionsupporting
confidence: 91%
“…However, methodological problems may have influenced the results of this study. For example, a signal loss in the globus pallidus, caused by its magnetic susceptibility effect with the T2-weighted spin-echo sequence (Schenker et al, 1993), may limit the dorsal delineation of the ROI. Furthermore, in linear measurements the angle of the section plane affects the thickness of the tissue.…”
Section: Age and Disease-related Changes In The Magnocellular Basal Cmentioning
confidence: 99%
“…There are a number of possible interpretations for this finding. For example, it is well known that iron concentrations, which can affect MR signal intensity, increase with age and are most prominent in the basal ganglia (Schenker et al, 1993;Vymazal et al, 1995). Thus, greater iron deposition could result in less activity in this region for adults.…”
Section: Developmental Differences Within Disparate Brain Regionsmentioning
confidence: 99%